Land And Water Management Option of Tidal Lowland Reclamation Area to Support Rice Production (A Case Study in Delta Sugihan Kanan of South Sumatra Indonesia) - Momon Sodik Imanudin; Bakri Bakri; Muhammad Edi Armanto; Budi Indra Setiawan; Ratmini S NP (Center for Journal Management and Publication, 2018)
The main problem for agriculture at tidal lowland swamp is low soil quality and high acidity of soil and high water. The research objective was to investigate how far the effort in increasing tertiary canal network to improve water quality (increasing pH and reducinf iron) in channel and tertiary plot. Field study was conducted at Bandarjaya Village of Jalur 25, Delta Sugihan Kanan, South Sumatra. Field activities were consisted of network investigationÂ land use and farm enterprise system which located at Primr 13 of Sugihan Kiri and Primer 25 of Sugihan Kanan. The network improvement perfomance was conducted by constructing micro water management (installed the tertiary gate and developen quartey canal) at tertiary plot which consisted of collector channel, sub tertiary channel and control plot which was outfall at quarterly channel downstream end. Water gate having goose neck pipe system was constructed to control water table in tertiary channel. Results of field study showed that land use at the study area was still dominated by rice crop with magnitude of 83% and the rest of 17% was used for rubber plantation, orange planation and mix plantation. The depth of phyrite layer was in the range of 60 to 100 cm below soil surface. Water table surface in October was in the range of 10 to 35 cm. Field adaptation showed that water gate was operated in closed condition (water retention) during vegetative phase. Water retention showed significant to improve rice yield in which water table since November had increased from -10 cm to flooding condition of 15 cm in January. This condition provide sufficient water for rice crop which was similar as the result found at irrigation area. The addition of ameliorant substances such as coconut fiber, and sand semen block at outfall of tertiary and kuartely channels also increase water quality in which water pH was increased fromÂ 2.95 to 3.7 and iron concentration was decreased from 4.01 to 0.32 mg/liter. Rice yield was increased from average production of 2 ton/ha to 3 ton/ha. This low production was due to land flushing process which need longer time process for at least 2 to 3 years from current condition as well as other production inputs such as fertilization and ameliorant substances.